Assessment of Videolaryngostroboscopy Images Based on Visible Vessels Of Vocal Folds - Turkmen, H. Irem; Karsligil, M. Elif; Kocak, Ismail (IEEE, 2012)
Extraction of vessel structures and the vessel features automatically forms an essential step for computer-aided diagnosis. Visible vessels of vocal folds become a diagnostic aid for vocal fold pathologies by publication of limited number of researches which analyze the effects of vocal fold pathologies on visual characteristics of blood vessels. In this paper we present a novel system that extracts blood vessels centerlines on vocal folds images and detects pathologically altered vocal folds exploiting visual characteristics of vessels.
Keywords: Blood Vessel Detection; Videolaryngostroboscopy; Vocal Fold Pathologies; Engineering